AKT1 and TRH1 are required during root hair elongation in Arabidopsis. - Desbrosses, G; Josefsson, C; Rigas, S; Hatzopoulos, P; Dolan, L (2003)
TRH1 is a member of the AtKT/AtKUP/AtHAK family of potassium carriers that is required for root hair elongation and AKT1 is an inward rectifying potassium channel expressed in the root epidermis, endodermis and cortex of Arabidopsis thaliana. Plants homozygous for the trh1-1 mutation form short root hairs. The Trh1(-) phenotype cannot be suppressed by growing plants homozygous for the trh1-1 mutation in the presence of high external KCl concentration. This indicates an absolute requirement for TRH1 in root hair tip growth. Plants homozygous for the akt1-1 mutation develop longer root hairs than the wild type when grown in 0 mM external potassium, but develop shorter hairs than the wild type when grown in higher concentrations [>10 mM] of potassium. These data indicate that both TRH1 and AKT1 are active in the root hair over a wide range of external potassium concentrations, but suggest they have different functions in the growing hair cell.